Human primary somatosensory cortex is differentially involved in vibrotaction and nociception - Lenoir, Cédric (J Neurophysiol, 2017)
The role of the primary somatosensory cortex (S1) in vibrotaction is well established. In contrast, its involvement in nociception is still debated. Here we test whether S1 is similarly involved in the processing of nonnociceptive and nociceptive somatosensory input in humans by comparing the aftereffects of high-definition transcranial direct current stimulation (HD-tDCS) of S1 on the event-related potentials (ERPs) elicited by nonnociceptive and nociceptive somatosensory stimuli delivered to the ipsilateral and contralateral hands. Cathodal HD-tDCS significantly affected the responses to nonnociceptive somatosensory stimuli delivered to the contralateral hand: both early-latency ERPs from within S1 (N20 wave elicited by transcutaneous electrical stimulation of median nerve) and late-latency ERPs elicited outside S1 (N120 wave elicited by short-lasting mechanical vibrations delivered to index fingertip, thought to originate from bilateral operculo-insular and cingulate cortices). These results support the notion that S1 constitutes an obligatory relay for the cortical processing of nonnociceptive tactile input originating from the contralateral hemibody. Contrasting with this asymmetric effect of HD-tDCS on the responses to nonnociceptive somatosensory input, HD-tDCS over the sensorimotor cortex led to a bilateral and symmetric reduction of the magnitude of the N240 wave of nociceptive laser-evoked potentials elicited by stimulation of the hand dorsum. Taken together, our results demonstrate in humans a differential involvement of S1 in vibrotaction and nociception. NEW & NOTEWORTHY Whereas the role of the primary somatosensory cortex (S1) in vibrotaction is well established, its involvement in nociception remains strongly debated. By assessing, in healthy volunteers, the effect of high-definition transcranial direct current stimulation over S1, we demonstrate a differential involvement of S1 in vibrotaction and nociception.